1970
DOI: 10.3126/nje.v1i2.5137
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Serological Markers in Viral Hepatitis and Non Alcoholic Fatty Liver Disease. A Comparative Study in Tertiary Care Hospital of Western Nepal

Abstract: Background: Liver diseases is apparently increasing and emerging as a major public health problem. Worldwide,  chronic hepatitis B has  become  the tenth leading cause of death  and  persons infected with chronic hepatitis B virus (HBV) and hepatitis C virus (HCV), are about 350 million and  125 million respectively. The aim of current retrospective comparative study was concerned primarily to evaluate the significance of non invasive serological markers for diagnosing liver diseases and their predictive impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The finding of De Ritis ratio 1.2204 ± 0.17954 (p = 0.005) in patients with NAFLD in our study suggests the presence of fibrosis or cirrhosis, which is not consistent with the study done by Mittal in 2011 at Manipal College of Medical Sciences, Pokhara, Nepal. [16] The disparity of result because the patient at Manipal Medical College may be in initial stage of NAFLD (steatosis), before advancement of fibrosis and cirrhosis.…”
Section: Mean Of De Ritis Ratio Was Compared Between Control and Eachmentioning
confidence: 99%
“…The finding of De Ritis ratio 1.2204 ± 0.17954 (p = 0.005) in patients with NAFLD in our study suggests the presence of fibrosis or cirrhosis, which is not consistent with the study done by Mittal in 2011 at Manipal College of Medical Sciences, Pokhara, Nepal. [16] The disparity of result because the patient at Manipal Medical College may be in initial stage of NAFLD (steatosis), before advancement of fibrosis and cirrhosis.…”
Section: Mean Of De Ritis Ratio Was Compared Between Control and Eachmentioning
confidence: 99%
“…A study by Mittal et al 86 at Pokhara, Nepal reported that the prevalence of NAFLD was 17%. Mild-to-moderate elevations in serum levels of aspartate aminotransferase (43.42–49.49 IU/L) and ALT (43.90–53.92 IU/L) were the most common laboratory abnormalities found in patients with NAFLD.…”
Section: Prevalence and Association In Different South Asian Countrymentioning
confidence: 98%
“…A few years ago we conducted a bibliographic review of health and medical publications in English of research conducted in Nepal, and the majority of this research was quantitative 17 , which is good for a journal like Nepal Journal of Epidemiology, but like in many low-income countries there is a need for further research capacity building [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Editorialmentioning
confidence: 99%